2014
DOI: 10.31018/jans.v6i2.515
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age of plantation on seed characters and growth performance of Tokopatta (Livistona jinkensiana Griff.) seedling

Abstract: Tokopatta palm (Livistona jinkensiana) is a valuable non timber multiple end uses forest species of Arunachal Pradesh. In order to establish improved plantation, the production of quality seedling of this species is essential. The present study was undertaken to determine tree age effects on seed characters, seed germination and performance of seedlings. The 500 seeds sample from each plantations aged 18, 25, 35, 45, 54, 63 and 74 years old around Pasighat town under East Siang district, Arunachal Pradesh, Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The maximum rate appeared in the intermediate age class (30 cm class for S. torminalis and 33 cm class for P. echinata, respectively). Similarly, Lyngdoh et al (2014) found that seeds collected from intermediate aged trees (i.e., 45 years old) of Livistona jinkensiana Griff. consistently had greater weight and germination rates compared to seeds collected from trees 18-35 years of age, and 54-74 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum rate appeared in the intermediate age class (30 cm class for S. torminalis and 33 cm class for P. echinata, respectively). Similarly, Lyngdoh et al (2014) found that seeds collected from intermediate aged trees (i.e., 45 years old) of Livistona jinkensiana Griff. consistently had greater weight and germination rates compared to seeds collected from trees 18-35 years of age, and 54-74 years of age.…”
Section: Discussionmentioning
confidence: 99%